2021
DOI: 10.1371/journal.pone.0254082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Isoniazid Preventive Therapy on Tuberculosis incidence among people living with HIV: A secondary data analysis using Inverse Probability Weighting of individuals attending HIV care and treatment clinics in Tanzania

Abstract: Background Information on how well Isoniazid Preventive Therapy (IPT) works on reducing TB incidence among people living with HIV (PLHIV) in routine settings using robust statistical methods to establish causality in observational studies is scarce. Objectives To evaluate the effectiveness of IPT in routine clinical settings by comparing TB incidence between IPT and non-IPT groups. Methods We used data from PLHIV enrolled in 315 HIV care and treatment clinic from January 2012 to December 2016. We used Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…1,7 Preventative therapies, including 6-9 months of isoniazid and more recently tested shorter courses of multiple drugs, like 3 months of rifapentine and isoniazid (3HP), have been successful in reducing the short-term risk of progression to ATB in PLWH. [8][9][10] The impact of TB prevention therapies has been limited by the difficulty of diagnostic testing for LTBI. The tuberculin skin test (TST) uses purified protein derivative (PPD) from Mtb and has significant rates of cross-reactivity with the M. bovis BCG strain used to vaccinate infants in TB endemic countries.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Preventative therapies, including 6-9 months of isoniazid and more recently tested shorter courses of multiple drugs, like 3 months of rifapentine and isoniazid (3HP), have been successful in reducing the short-term risk of progression to ATB in PLWH. [8][9][10] The impact of TB prevention therapies has been limited by the difficulty of diagnostic testing for LTBI. The tuberculin skin test (TST) uses purified protein derivative (PPD) from Mtb and has significant rates of cross-reactivity with the M. bovis BCG strain used to vaccinate infants in TB endemic countries.…”
Section: Introductionmentioning
confidence: 99%
“…This difference might be attributed to the different study design and sampling techniques used. Other studies reported similar findings of lower incidence rates among PLHIV that completed IPT therapy than those who were not IPT therapy 17 19 .…”
Section: Discussionmentioning
confidence: 52%
“…A number of studies have reported that IPT significantly reduces incidence of TB among PLHIV after completion of the 6 month period of treatment 17 19 . This study recorded a TB prevalence of 5.8% among PLHIV who had completed the 6 months period of IPT treatment, which is lower than 8.1% and 9.0% reported respectively in studies conducted in Ethiopia 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Tanzania uses isoniazid preventive treatment (IPT) for prevention of active TB disease among PLHIV since 2010 (7). The IPT involves the use of self-administered isoniazid daily for 6 to 9 months (8,9).…”
Section: Introductionmentioning
confidence: 99%